The association between social comparison in social media, body image concerns and eating disorder symptoms: A systematic review and meta-analysis - Bonfanti, Rubinia Celeste; Melchiori, Francesco; Teti, Arianna; Albano, Gaia; Raffard, Stéphane; Rodgers, Rachel; Lo Coco, Gianluca (Body image, 2025)
Research has found that high social media use is associated with a greater tendency to compare oneself with others, which in turn may heighten body image concerns and problematic eating behaviours. The aim of this systematic review and meta-analysis was to examine the mean association between online social comparison and body image concerns, eating disorder behaviours and positive body image. Eligible articles published between 2008 and 2024 were searched for in scientific databases. A random-effects meta-analysis was conducted to investigate the direct correlation between social comparison and body image and eating disorder outcomes. Results from 83 studies with 55,440 participants indicated that the weighted average correlation between higher online social comparison and greater body image concerns was significant (r = .454; 95 % CI = 0.409–0.498), as was the correlation between higher social comparison and eating disorder symptoms (r = 0.36; 95 % CI: 0.28–0.43). The mean association between higher social comparison and lower positive body image was also significant (r = -0.242; 95 % CI: −0.329 to −0.155). Meta-regression analysis revealed that the quality of studies, type of social media, country, type of social comparison, percentage of female participants moderated the associations. Findings revealed a moderate size association between higher online social comparison tendencies and worse body image and eating disorder symptoms outcomes, highlighting the need to develop interventions and policies to minimize appearance comparisons on social media. •High social media use is associated with a tendency to compare oneself with others.•Association between higher online social comparison and greater body image concerns.•Association between higher online social comparison and lower positive body image.•Association between higher online social comparison and greater eating disorders.